A sectored receiver for infrared wireless networks - Alves, L. N. (2000)
This paper presents an experimental sectored receiver for infrared wireless networks. The receiver comprises two sectors, each with a switched gain front-end and a signal-to-noise ratio estimator. These are then interconnected with a best-sector selector unit, able to compensate the gain switching characteristics of the front-ends. The circuit has been designed in a 0.8 μm CMOS technology.